Evaluasi Mutu Internal (EMI) Program Studi Akreditasi “A” Universitas Negeri Makassar Tahun 2019 - Agung Widhi Kurniawan; Sapto Haryoko; Herman Herman (Seminar Nasional LP2M UNM, 2019)
The results showed that the overall profile of the study program showed a balanced ratio between lecturers and students. The structure of the study program consists of the head of the study program, the secretary and the head of the laboratory as well as lecturers and students. The overall performance description is in the good category for each standardized average value. Nevertheless there are still some standards whose average values are still in major and minor improvements. The internal quality evaluation that is carried out every year is expected to result in an improvement in the study program accreditation ranking by BAN-PT. The audit findings show that the Dean and Chair of the Study Program have not fully understood and are aware of their duties and obligations in their respective work environments. Of the audited standards are still dominated by standards relating to the first dharma, namely education and teaching while for the research and community service darma is still relatively low. Recapitulation of the achievements of each study program as a whole shows the quality assurance phasing of the improvement of some minor standards such as standards 1, 2, 3, 4, 5, 6.7 and major improvements to standards 8, 9 and 10. Nevertheless there are still some standards the average value is still in major and minor improvements. This condition, of course, must be a concern of all parties so that quality culture is a priority.